High-intensity focused ultrasound (HIFU) in the treatment of prostate cancer (literature review) - V. A. Solovov; A. A. Tyurin (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Prostate cancer remains one of the most common urological malignancies. This article aims to describe the experience of using high-intensity focused ultrasound (HIFU), a non-invasive method for the treatment of prostate cancer, and to summarize the results of latest studies on this problem.